Faktor Penyebab Terjadinya Keterlambatan Pengiriman Barang ke Consignee pada PT. Lex Indonesia - Akbar Prakoso (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2024)
Lex Indonesia is a company engaged in the field of transportation and shipping services that serve the public in sending packages and documents door to door to all corners of Indonesia. The problem in this thesis is the factors that cause delays in shipping goods to consignees. The purpose of this study is to determine the factors that cause delays in shipping goods to consignees at PT. Lex Indonesia Jakarta in 2020 and find effective solutions and actions. Based on the results of the analysis using the fishbone diagram method used, five influencing factors were obtained, namely, the number of employees is not sufficient to handle the shipping process, bonuses are not given to employees to increase work enthusiasm, there are obstacles in the process of handling shipping goods, the fleet available to support shipping activities is inadequate, fleet maintenance has not been carried out properly and correctly. The root cause solution of the five factors, namely suggesting conducting a selection management analysis by creating positions and HR planning that are useful for finding out how many prospective employees are needed, management should create a program that motivates employees in the form of bonuses to increase work enthusiasm, pay attention to problems related to labor by creating a job training program plan, provide a special budget seriously to add new fleets, conduct routine fleet maintenance schedule evaluations by creating a proper maintenance system and preventive measures to overcome damage and provide warnings in the form of sanctions or notifications to each employee about the procedures for operating the fleet in accordance with the procedure.